Early vertical correction of the deep curve of Spee - Renato Parsekian Martins
ABSTRACT Even though few technological advancements have occurred in Orthodontics recently, the search for more efficient treatments continues. This paper analyses how to accelerate and improve one of the most arduous phases of orthodontic treatment, i.e., correction of the curve of Spee. The leveling of a deep curve of Spee can happen simultaneously with the alignment phase through a method called Early Vertical Correction (EVC). This technique uses two cantilevers affixed to the initial flexible archwire. This paper describes the force system produced by EVC and how to control its side effects. The EVC can reduce treatment time in malocclusions with deep curves of Spee, by combining two phases of the therapy, which clinicians ordinarily pursue sequentially.